Resuscitation planning on a subacute geriatric evaluation and management ward. (22nd February 2019) - Strasser, Rupert; Smith, Roger; Yates, Paul; Reid, David; Katz, Benny
Abstract : Objectives: To describe the use of acute resuscitation plans (ARPs) among patients on a subacute geriatric ward and to identify factors associated with use of ARPs in these patients. Methods: The hospital records of all patients admitted to the geriatric medicine ward in 2016 were retrospectively audited. Results: An ARP was completed before separation for 333/442 (75.3%) admissions. In the event of arrest, 240 (54.3%) patients had an ARP specifying "care of the dying", 93 (21.0%) had an ARP specifying "cardiopulmonary resuscitation" and 109 (24.7%) had no resuscitation plan. Age 85‐94 years (OR 1.65, P  = 0.04) and ≥95 years (OR 9.59, P  = 0.003), as well as Charlson index of comorbidity ≥2 (OR 3.4, P  < 0.001), Australian‐born (OR 2.09, P  = 0.002) and admission during October‐December (OR 3.81, P  < 0.001) were independently associated with increased use of ARPs. Conclusions: Acute resuscitation plan use was associated with older age, higher comorbidity, birth in Australia and admission later in the year.